Polylactic Acid as a Potential Alternatives of Traditional Plastic Packagings in Food Industry - Horváth, Tibor; Szabó, Tamás József; Marossy, Kálmán (International Journal of Engineering and Management Sciences, 2020)
Huge quantity of synthetic polymers is used as packaging materials in different fields of food industries. A significant part of these polymers applied as a primary, direct food contact construction. The scoped application area is the sweet industry. In this field Polystyrol (PS), Polypropylene (PP) and Polyethylene terephthalate (PET) have used but during the last fifteen years the usage of PET has been grown. In one hand the price of this material is efficient, form other hand the PET is the one of the most safe (for food industrial applications) petrol chemical plastic that can be used as primary or secondary food contact packaging material. To maximize the customer safety and minimize the environmental impact of traditional PET, a new bio-sourced and bio-degradable alternative polymer aimed to be used in this special food industrial segment. One of the potential alternatives is the Polylactic acid (PLA) that would be a possible substitute as it is compostable and produced from renewable sources and has good physical and mechanical properties [1].